Randomized phase III trial of pemetrexed versus docetaxel in patients with non-small-cell lung cancer previously treated with chemotherapy: JCO flashback - Hanna, Nasser; Shepherd, Frances A.; Fossella, Frank V.; Pereira, Jose R.; De Marinis, Filippo; Pawel, Joachim von; Gatzemeier, Ulrich; Tsao, Thomas Chang Yao; Pless, Miklos; Muller, Thomas; Lim, Hong-Liang; Desch, Christopher; et al. (Journal of clinical oncology, 2023)
PURPOSE - To compare the efficacy and toxicity of pemetrexed versus docetaxel in patients with advanced non-small-cell lung cancer (NSCLC) previously treated with chemotherapy. - PATIENTS AND METHODS - Eligible patients had a performance status 0 to 2, previous treatment with one prior chemotherapy regimen for advanced NSCLC, and adequate organ function. Patients received pemetrexed 500 mg/m2 intravenously (IV) day 1 with vitamin B12, folic acid, and dexamethasone or docetaxel 75 mg/m2 IV day 1 with dexamethasone every 21 days. The primary end point was overall survival. - RESULTS - Five hundred seventy-one patients were randomly assigned. Overall response rates were 9.1% and 8.8% (analysis of variance P = .105) for pemetrexed and docetaxel, respectively. Median progression-free survival was 2.9 months for each arm, and median survival time was 8.3 versus 7.9 months (P = not significant) for pemetrexed and docetaxel, respectively. The 1-year survival rate for each arm was 29.7%. Patients receiving docetaxel were more likely to have grade 3 or 4 neutropenia (40.2% v 5.3%; P < .001), febrile neutropenia (12.7% v 1.9%; P < .001), neutropenia with infections (3.3% v 0.0%; P = .004), hospitalizations for neutropenic fever (13.4% v 1.5%; P < .001), hospitalizations due to other drug related adverse events (10.5% v 6.4%; P = .092), use of granulocyte colony-stimulating factor support (19.2% v 2.6%, P < .001) and all grade alopecia (37.7% v 6.4%; P < .001) compared with patients receiving pemetrexed. - CONCLUSION - Treatment with pemetrexed resulted in clinically equivalent efficacy outcomes, but with significantly fewer side effects compared with docetaxel in the second-line treatment of patients with advanced NSCLC and should be considered a standard treatment option for second-line NSCLC when available.